Concrete material combination performance test method
By making standard samples and test samples at the concrete construction site, testing their expansion degree and observing the status of the mixture, the problem of difficulty in quickly finding out the fluctuations of various concrete components in the prior art is solved, and faster and more accurate compatibility detection and construction mix ratio control are achieved.
Patent Information
- Application Number
- CN202411911852.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to quickly find out the fluctuations of the various components of concrete materials, resulting in poor compatibility and increased difficulty in controlling the construction mix ratio.
A concrete material combination performance test method is used to determine whether the compatibility of new raw materials meets the requirements by making standard samples and test samples, testing their expansion at different time points and observing the state of the mixture.
It can find out the fluctuations of various concrete components faster and more accurately, quickly solve the problem of fluctuations in concrete performance, and is suitable for quality control at concrete construction sites.
Smart Images

Figure BDA0005205887490000051 
Figure BDA0005205887490000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete, and in particular to a method for testing the combined performance of concrete materials. Background Art
[0002] At present, with the development of cement concrete mix design technology, the application of large-volume mineral admixtures and the diversity of concrete admixtures, the types of concrete composite materials have increased, resulting in an increase in the types of materials entering the construction site. The combination of different batches of concrete raw materials is prone to poor compatibility, which in turn increases the difficulty of controlling the concrete construction mix ratio. Changes in certain raw materials during the concrete production process make it difficult for concrete performance to meet construction requirements. At present, the existing technical detection methods can only detect whether the compatibility of concrete composite materials is good. When the compatibility index does not meet the index requirements, the following problems will also occur:
[0003] 1. It is unclear what causes the poor compatibility of the mixture after the components are mixed, such as sample segregation and water bleeding;
[0004] 2. It is not possible to quickly find out whether there is quality fluctuation in a certain combination of materials in the mixture.
[0005] Therefore, there is an urgent need to find an experimental method that can solve the above problems. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for testing the combined performance of concrete materials.
[0007] In order to achieve the technical effects of the present invention, the following technical solutions are adopted:
[0008] A test method for combined performance of concrete materials, the test method is:
[0009] Step 1): Prepare standard samples using the raw materials and proportions actually used at the project construction site, test the expansion of the standard samples at one or several time points, and observe the state of the mixture; the raw materials include cement, mineral admixtures, fine aggregates and admixtures;
[0010] Step 2): Replace one of the corresponding components in the raw materials of step 1) with a new raw material, prepare a test sample according to the same proportion and preparation method as step 1), and test the expansion of the test sample at the same time point and observe the state of the test sample mixture using the same method as the standard sample;
[0011] Step 3): Compare the expansion data and mixture state of the test sample and the standard sample at the same time point to determine whether the compatibility of the new raw material meets the requirements.
[0012] As a further improvement, the preparation method of the standard sample includes: adding cement, mineral admixture and fine aggregate into a stirring device for pre-stirring, then mixing the admixture with water evenly and adding it into the stirring device for stirring, and obtaining a mixture after stirring, that is, a standard sample; the testing method of the expansion degree includes: adding the mixture into a mortar expansion degree cylinder to measure the expansion degree; when it is necessary to measure the expansion degree at a certain time starting from the time of adding water again, pouring the mixture that has been tested for expansion degree back into the stirring device and placing it for a period of time, after stirring for a certain period of time, adding the stirred mixture into the mortar expansion degree cylinder to measure the expansion degree; the observation of the state of the mixture is to observe the state of the mixture during the test; the new raw materials are newly incoming raw materials.
[0013] As a further improvement, the step 1) includes:
[0014] 1.1 Place the glass plate horizontally, and wipe the glass plate, mortar expansion cylinder, mixing blades of cement mortar mixer and the inner wall of mixing pot evenly with a wet cloth to make their surfaces moist;
[0015] 1.2 Place the mortar expansion cylinder in the center of the glass plate and cover it with a wet cloth for later use;
[0016] 1.3 Weigh cement, mineral admixture, fine aggregate, water and admixture according to the proportion of the mixture and set aside;
[0017] 1.4 First, add cement, mineral admixtures and fine aggregates into the mixing pot and pre-mix for 10 seconds, then mix the admixtures and water evenly and add them into the mixing pot;
[0018] 1.5 Start the cement mortar mixer and mix according to the cement mortar mixer program, starting from the moment of adding water;
[0019] 1.6 After stirring, the mixture is obtained. Pour the mixture into the mortar expansion cylinder twice, pouring 1 / 2 of the cylinder height each time, and use a tamping rod to tamp 15 times evenly in a clockwise direction from the edge to the center; when tamping the bottom layer, the tamping rod should penetrate the depth of the mixture in the cylinder, and when tamping the second layer, the tamping rod should penetrate the current layer to the surface of the next layer; after tamping, scrape the surface of the mixture flat, lift the mortar expansion cylinder vertically upward slowly and evenly, and after 10 seconds, use a steel ruler to measure the maximum diameters of the mixture on the glass plate in two directions perpendicular to each other, and take the average value as the expansion;
[0020] 1.7 Pour the mixture sample back into the mixing pot and cover the mixing pot with a wet cloth. Start the mixer of the cement mortar mixer 30min, 60min and 120min after the start of the timing. Mix rapidly for 1min and then measure the time loss of the mixture expansion according to the steps in 1.6. Observe and record the changes in the state of the mixture during the test.
[0021] As a further improvement, the mineral admixture includes one or both of mineral powder and fly ash.
[0022] As a further improvement, the fine aggregate includes machine-made sand and river sand.
[0023] As a further improvement, the raw materials include 368 parts of cement, 197 parts of mineral admixtures, 1247 parts of fine aggregates and 6.2 parts of admixtures; and the amount of water used is 248 parts.
[0024] As a further improvement, the total volume of the standard sample is greater than 1.5 liters.
[0025] As a further improvement, the total volume of the standard sample is 1.5 liters to 5 liters.
[0026] The present invention provides a method for testing the combined performance of concrete materials, which has the following beneficial effects:
[0027] The present invention can find out the fluctuation of each component material of concrete more quickly and accurately by comparing the existing material test data (test sample test data) with the standard sample. Compared with the existing technology that only conducts compatibility tests on each component material and the substitute (it can only test whether each combined material is compatible with the substitute), this test method can quickly find out the factors causing the fluctuation of concrete, and quickly solve the problem of fluctuation of concrete performance through targeted technical adjustments. This method can be better applied to concrete construction sites. DETAILED DESCRIPTION
[0028] A test method for combined performance of concrete materials, the test method is:
[0029] Step 1): Prepare standard samples using the raw materials and proportions actually used at the project construction site, test the expansion of the standard samples at one or several time points, and observe the state of the mixture; the raw materials include cement, mineral admixtures, fine aggregates and admixtures;
[0030] Step 2): Use new raw materials to replace a corresponding component in the raw materials of step 1), make test samples according to the same proportion and preparation method as step 1), and use the same method as the standard sample to test the expansion of the test sample at the same time point and observe the state of the test sample mixture; corresponding refers to the raw materials, what substances are not added, the new raw materials are added with the same amount; when the raw materials are composed of cement, mineral admixtures, fine aggregates and admixtures, since cement, mineral admixtures, fine aggregates and admixtures are brought in every day, but the batches are different. For example, when the admixture is a water reducer, and the standard sample contains 1 part of cement, 1 part of mineral admixtures, 1 part of fine aggregates and 1 part of water reducer, use new raw materials (new water reducer) to replace a corresponding component of the raw materials in step 1), the water reducer, then the formula of the test sample contains 1 part of cement, 1 part of mineral admixtures, 1 part of fine aggregates and 1 part of new water reducer.
[0031] Step 3): Compare the expansion data and mixture state of the test sample and the standard sample at the same time point to determine whether the compatibility of the new raw material meets the requirements.
[0032] Preferably, the preparation method of the standard sample includes: adding cement, mineral admixture and fine aggregate into a stirring device for pre-stirring, then mixing the admixture with water evenly and adding it into the stirring device for stirring, and obtaining a mixture after stirring, that is, a standard sample; the testing method of the expansion degree includes: adding the mixture into a mortar expansion degree cylinder to measure the expansion degree; when it is necessary to measure the expansion degree at a certain time starting from the time of adding water (which is also the time of adding the evenly mixed admixture and water), the mixture that has been tested for expansion degree is poured back into the stirring device and placed for a period of time. After stirring for a certain period of time, the stirred mixture is added into a mortar expansion degree cylinder to measure the expansion degree; the observation of the state of the mixture is to observe the state of the mixture during the test; the new raw materials are newly incoming raw materials.
[0033] Example 1
[0034] 1. Preparation and testing of standard samples
[0035] 1.1 Instruments and equipment used in the test
[0036] Cement mortar mixer; mortar expansion cylinder: upper inner diameter 50mm±0.5mm, lower inner diameter 100mm±0.5mm, height 150mm±0.5mm; tamping rod: diameter 8mm±0.2mm, length 300mm±3mm; glass plate: 500mm*500mm*5mm, steel ruler: measuring range 500mm, graduation value 1mm; balance: graduation value 0.01g; platform scale: graduation value 1g.
[0037] 1.2. Test raw materials, mix ratio and environmental conditions
[0038] 1.2.1 The cement, mineral admixtures, fine aggregates and admixtures actually used at the project construction site are used; in this embodiment, the fine aggregate is the machine-made sand actually used at the project construction site.
[0039] 1.2.2 The machine-made sand actually used at the project site was screened out with a particle size greater than 5 mm before the test, and the sample was in a dry state;
[0040] 1.2.3 The mix proportion should be the mix after removing the coarse aggregate from the concrete actually used in the project, and the total amount of the test mix should not be less than 1.5L. It can be greater than or equal to 1.5L, for example, the total volume can be selected from 1.5L to 5L.
[0041] 1.2.4 The test shall be carried out under standard test conditions. The test room temperature shall be maintained at 20℃±2℃ and the relative humidity shall not be lower than 50%.
[0042] 1.3. Preparation and testing methods of standard samples
[0043] 1.3.1 Place the glass plate horizontally, and wipe the glass plate, mortar expansion cylinder, mixing blades of cement mortar mixer and the inner wall of mixing pot evenly with a wet cloth to make their surfaces moist;
[0044] 1.3.2 Place the mortar expansion cylinder in the center of the glass plate and cover it with a wet cloth for later use;
[0045] 1.3.3 According to the proportion of the mixture, weigh 368g of cement, 197g of mineral admixture, 1247g of fine aggregate, 248g of water and 6.2g of admixture for use; the mineral admixture is 98.5g of mineral powder and 98.5g of fly ash.
[0046] 1.3.4 First add cement, mineral admixtures and fine aggregate into the mixing pot and pre-mix for 10 seconds, then mix the admixtures and water evenly and add them into the mixing pot.
[0047] 1.3.5 Immediately start the cement mortar mixer and mix according to the cement mortar mixer program (the automatic control program specified in "Planetary Cement Mortar Mixer" JC / T681-2022 can be used for mixing (but no sand is added during mixing)), and start timing from the time of adding water (that is, start timing from the time the admixture and water are evenly mixed and added to the mixing pot);
[0048] 1.3.6 After stirring, the mixture is obtained. Pour the mixture into the mortar expansion cylinder twice, pouring 1 / 2 of the cylinder height each time, and use a tamping rod to tamp 15 times evenly in a clockwise direction from the edge to the center. Each tamping should be evenly distributed on the cross section; when tamping the bottom layer, the tamping rod should penetrate the depth of the mixture in the cylinder, and when tamping the second layer, the tamping rod should penetrate the current layer to the surface of the next layer; after tamping, scrape the surface of the mixture flat, slowly and evenly lift the mortar expansion cylinder vertically upward (it can be lifted evenly within 2 to 3 seconds), and after 10 seconds, use a steel ruler to measure the maximum diameters of the mixture dropped on the glass plate in two directions perpendicular to each other, and take the average value as the expansion (i.e., the initial expansion (mm));
[0049] 1.3.7 Pour the poured mixture back into the mixing pot and cover the mixing pot with a wet cloth. Start the mixer of the cement mortar mixer 30min, 60min, and 120min after the start of the timing, stir quickly for 1min, and then measure the time loss of the expansion degree of the mixed material after stirring (i.e. 30min expansion degree (mm), 60min expansion degree (mm), 120min expansion degree (mm)) according to the steps in 1.3.6; observe and record the changes in the state of the mixture during the test. Generally, it is the state of the mixture when it is placed in the mixing pot after stirring.
[0050] The raw materials used for the standard sample in this embodiment are: the standard sample is prepared by using the concrete mix raw materials used in the actual construction of Section A of the Guangxi Guilin Outer Ring Expressway General Contracting Project. That is, the raw materials are 368g of cement, 98.5g of mineral powder, 98.5g of fly ash, 1247g of machine-made sand, and 6.2g of admixture. The water used in the standard sample is 248g.
[0051] The preparation method and mix ratio of the test sample A are the same as those of the standard sample, with the only difference being that the admixture of the test sample is a new batch of admixture A from the concrete mixing station of the Guilin Outer Ring Expressway General Contracting Project (the admixture of the standard sample and the admixture of the test sample A are of the same model, but in different batches), and the other raw materials of the test sample A are the same as those of the standard sample, and the batches are also the same. That is, the raw materials used in the test sample A are 368g of cement, 98.5g of mineral powder, 98.5g of fly ash, 1247g of machine-made sand, and 6.2g of the new admixture A. The water used in the test sample A is 248g.
[0052] The test results of standard sample and test sample A are shown in Table 1.
[0053] Table 1 Test comparison data table
[0054]
[0055] Whether the compatibility of the test sample meets the requirements can be determined based on the actual conditions of the workability requirements of cement concrete at the construction site. This regulation stipulates that if the difference between the test value of the test sample at a certain moment and the reference value of the standard sample at the same moment is less than or equal to 10mm and the state of the mixture is no segregation and bleeding, the compatibility of the new raw materials meets the requirements, otherwise it does not meet the requirements.
[0056] By comparing the test values of field test sample A with the benchmark values of standard samples, it was found that since the deviations between the test values of field test sample A for 60min expansion and 120min expansion and the benchmark values of standard samples were both greater than 10mm, the compatibility of the newly-arrived admixture A was poor and did not meet the design requirements, and the admixture needed to be re-optimized.
[0057] In this embodiment, although the state of the mixture has not separated and bled water, it cannot be determined that the compatibility meets the requirements. It is necessary to combine the expansion degree and the state of the mixture in different time periods to determine whether the compatibility meets the requirements.
[0058] Example 2
[0059] The standard sample of Example 2 adopts the standard sample data and mixture state measured in Example 1. Whether the compatibility of the test sample meets the requirements is also based on the standard: if the detection value of the test sample at a certain moment differs from the reference value of the standard sample at the same moment by less than or equal to 10mm and the mixture state is without segregation and exudation, the compatibility of the new raw material meets the requirements, otherwise it does not meet the requirements.
[0060] The preparation method and mix ratio of test sample B are the same as those of the standard sample. The difference from the standard sample is that the sand of test sample B is a batch of newly introduced machine-made sand from the concrete mixing station of the Guilin Outer Ring Expressway General Contracting Project. The other raw materials of test sample B are the same as those of the standard sample, and the batch is also the same. That is, the raw materials used in test sample B are 368g of cement, 98.5g of mineral powder, 98.5g of fly ash, 1247g of newly introduced machine-made sand, and 6.2g of admixture; the water used in test sample B is 248g.
[0061] The test results of standard sample and test sample B are shown in Table 2.
[0062] Table 2 Test comparison data table
[0063]
[0064] By comparing the test value of field test sample B with the benchmark value of standard sample, it was found that the data difference between the test value of field test sample B and the benchmark value of standard sample was within 10mm, the state of the mixture was consistent, and the new batch of machine-made sand had good compatibility with other concrete composite materials and met the design requirements.
[0065] The method of the present invention specifies a test method for the combined performance of raw materials used in concrete, which can be used as an important method for controlling the stability of the combined raw materials of concrete during construction, can better control the quality of the raw materials entering the concrete site, and provide a guiding basis for concrete production.
[0066] This method is applicable to the quality control of raw materials such as cement, fine aggregate (such as machine-made sand, river sand), admixtures, mineral admixtures (such as fly ash, mineral powder) used in cement concrete at construction sites.
[0067] Test samples can also be called experimental samples or control samples.
[0068] The admixture used in Examples 1 and 2 of the present invention is admixture JD-R20, which can be sold by Guangxi Polyconcrete New Material Technology Co., Ltd. Admixture A is the newly-added admixture JD-R20.
[0069] Of course, in the present invention, other admixtures may also be used in the standard sample. If other admixtures are used in the standard sample, the corresponding test sample also uses other corresponding admixtures.
[0070] In the present invention, whether the compatibility meets the requirements can be determined according to the requirements of the project construction site. It is not necessary that the difference between the detection value of the test sample at a certain moment and the reference value of the standard sample at the same moment must be less than or equal to 10mm and the state of the mixture is no separation and exudation of water, that is, the compatibility of the new raw material meets the requirements.
[0071] The material components and proportions used in the standard sample can be determined according to the project construction site. The components and dosage can be changed according to the actual production situation.
[0072] The cement mortar mixer described in the present invention should comply with the relevant provisions of the current industry standard "Planetary Cement Mortar Mixer" JC / T681-2022, wherein the rapid mixing speed is based on the relevant provisions of the standard for high-speed mixing. Pre-mixing can be based on the relevant provisions of the standard for low-speed mixing.
[0073] The above is only a preferred embodiment of the present invention, and it cannot be used to limit the scope of the present invention. That is, all simple equivalent changes and modifications made according to the contents recorded in the claims and the invention specification are still within the scope of the claims of the present invention. In addition, the abstract and title are only used to assist in searching patent documents, and are not used to limit the scope of the rights of the present invention.
Claims
1. A method for testing the combined performance of concrete materials, characterized in that: The test method is: Step 1): Prepare standard samples using the raw materials and proportions actually used at the project construction site, test the expansion of the standard samples at one or several time points, and observe the state of the mixture; the raw materials include cement, mineral admixtures, fine aggregates and admixtures; Step 2): Replace one of the corresponding components in the raw materials of step 1) with a new raw material, prepare a test sample according to the same proportion and preparation method as step 1), and test the expansion of the test sample at the same time point and observe the state of the test sample mixture using the same method as the standard sample; Step 3): Compare the expansion data and mixture state of the test sample and the standard sample at the same time point to determine whether the compatibility of the new raw material meets the requirements.
2. A concrete material combination performance test method as claimed in claim 1, characterized in that: The preparation method of the standard sample includes: adding cement, mineral admixture and fine aggregate into a stirring device for pre-stirring, then mixing the admixture with water evenly and adding it into the stirring device for stirring, and obtaining a mixture after stirring, that is, a standard sample; the testing method of the expansion degree includes: adding the mixture into a mortar expansion degree cylinder to measure the expansion degree; when it is necessary to measure the expansion degree at a certain time starting from the time of adding water again, pouring the mixture that has been tested for expansion degree back into the stirring device and placing it for a required time, after stirring for a certain time, adding the stirred mixture into the mortar expansion degree cylinder to measure the expansion degree; the observation of the state of the mixture is to observe the state of the mixture during the test; the new raw materials are newly delivered raw materials.
3. A concrete material combination performance test method as claimed in claim 1, characterized in that: The step 1) comprises: 1.1 Place the glass plate horizontally, and wipe the glass plate, mortar expansion cylinder, mixing blades of cement mortar mixer and the inner wall of mixing pot evenly with a wet cloth to make their surfaces moist; 1.2 Place the mortar expansion cylinder in the center of the glass plate and cover it with a wet cloth for later use; 1.3 Weigh cement, mineral admixture, fine aggregate, water and admixture according to the proportion of the mixture and set aside; 1.4 First, add cement, mineral admixtures and fine aggregates into the mixing pot and pre-mix for 10 seconds, then mix the admixtures and water evenly and add them into the mixing pot; 1.5 Start the cement mortar mixer and mix according to the cement mortar mixer program, starting from the moment of adding water; 1.6 After stirring, the mixture is obtained. Pour the mixture into the mortar expansion cylinder twice, pouring 1 / 2 of the cylinder height each time, and use a tamping rod to tamp 15 times evenly in a clockwise direction from the edge to the center; when tamping the bottom layer, the tamping rod should penetrate the depth of the mixture in the cylinder, and when tamping the second layer, the tamping rod should penetrate the current layer to the surface of the next layer; after tamping, scrape the surface of the mixture flat, lift the mortar expansion cylinder vertically upward slowly and evenly, and after 10 seconds, use a steel ruler to measure the maximum diameters of the mixture on the glass plate in two directions perpendicular to each other, and take the average value as the expansion; 1.7 Pour the mixture sample back into the mixing pot and cover the mixing pot with a wet cloth. Start the mixer of the cement mortar mixer 30min, 60min and 120min after the start of the timing. Mix rapidly for 1min and then measure the time loss of the mixture expansion according to the steps in 1.
6. Observe and record the changes in the state of the mixture during the test.
4. A concrete material combination performance test method as claimed in claim 1, characterized in that: The mineral admixture includes one or both of mineral powder and fly ash.
5. A concrete material combination performance test method as claimed in claim 1, characterized in that: The fine aggregate includes machine-made sand and river sand.
6. A concrete material combination performance test method as claimed in claim 1, characterized in that: The raw materials include 368 parts of cement, 197 parts of mineral admixtures, 1247 parts of fine aggregates and 6.2 parts of admixtures; the amount of water used is 248 parts.
7. A concrete material combination performance test method as claimed in claim 1, characterized in that: The total volume of the standard sample is more than 1.5 liters.
8. A method for testing the combined performance of concrete materials as claimed in claim 6, characterized in that: The total volume of the standard sample is 1.5 liters to 5 liters.
Citation Information
Patent Citations
Method for testing adaptability between water reducing agent and concrete and expansion degree test device
CN104568660A
Method for quickly comparing and testing performance indexes of polycarboxylic acid concrete admixtures
CN110567847A
Method for detecting raw materials used in concrete production
CN113063931A
Method for preparing substitute material in related test process of fresh concrete
CN115490471A